Preliminary study on antecedents of sustainable construction among contracting companies operating in Malaysia - Bamgbade, Jibril Adewale; Kamaruddeen, Ahmed Mohammed; Mohd Nawi, Mohd Nasrun; Aziz, Zulkufli (Penerbit UTM Press, 2015)
There has been an increasing demand on the construction industry to incorporate sustainability practices and principles in their operations and construction products, considering the industry’s contribution to environmental degradation.It is therefore crucial for the construction industry to adopt sustainable construction, thereby reducing the negative impacts of construction activities on the environment.While there are several sustainable construction studies in Malaysia, a study that integrates innovativeness, culture, government support and sustainable construction in a single framework has not been given a considerable attention.The objectives of this study are to develop a framework that incorporates the antecedents of sustainable construction; and to assess the validity and reliability of the research instrument.Data were obtained from thirty respondents using a sixty-one item instrument. The data obtained were analyzed using SPSS software to assess the instrument’s reliability.The results of the Cronbach’s Alpha test reveal a strong internal reliability of the study’s constructs and the overall instrument.This paper complements the existing body of knowledge on sustainable construction.